Nursing care for critically ill patients with acute kidney injury: An integrative review - Murrugarra, Lais Kaori Sato; Lima, Ana Luisa Serrano; Dias, Giovana Munhoz; Sampaio, Giovana Tofoli; Fecchio, Carolina Amadeu; Costa, Sara Eleotério; Novais, Rafael Brendo; Luckner, Ana Clara; Santos, Lorraine de Souza; Sesnik, Heitor Hortensi; Santos, Gabriel Vale dos; Uema, Roberta Tognollo Borotta (Seven Editora, 2024)
Introduction: In the Intensive Care Unit, it is observed that Acute Kidney Injury is a very common comorbidity that culminates in the dysfunction of one of the most important organs. The main characteristics of this pathology are low diuresis output and increased serum creatinine. Objective: To identify in the literature what nursing care is provided for adult patients who develop acute kidney injury during hospitalization in the intensive care unit. Method: Integrative literature review, guided by the following research question formulated in accordance with the PICo strategy: What nursing care is provided to adult patients with acute kidney injury admitted to an intensive care unit? The search was carried out between April and May 2023 in the Virtual Health Library and PUBMED. Results: 515 articles were found and of these 461 were excluded because they did not correspond to the theme. 12 were not available in full, 30 did not answer the research question, totaling 8 articles for analysis. It was identified that nursing care for patients with acute kidney injury in the ICU goes beyond the kidney problem, focusing on the patient’s global well-being. No specific care for the disease was observed, only issues aimed at the critical patient as a whole. Conclusion: There is a high incidence of patients who develop acute kidney injury when admitted to the intensive care unit, however, even though the disease is reversible, it is observed that nurses have shallow knowledge on the subject, as it was not possible to find care prescribed directly for this purpose. DOI:https://doi.org/10.56238/sevened2024.001-041